Management of preparation of highly qualified decathleters based on the development of a competitive activity model - Tsyplenkova E.S. ,; Ogandganov A.L. ,; Salamatov M.B., (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a methodology for managing the training of highly qualified decathletes based on creating a model of competitive activity in decathlon. Methods and structure of the study. The scientific work includes an analysis of documentary materials, a method of mathematical statistics, and a pedagogical experiment. Results and conclusions. Based on the analysis of indicators of competitive activity in certain types of decathlon of the world's leading all-around athletes using regression analysis, a model of competitive activity in track and field decathlon was formed. The model of competitive activity allows: to compare the results of an athlete in certain types with the average statistical indicators for a given result in the decathlon, to analyze the results of a decathlete in certain types, to identify lagging and dominant types of decathlon for a given athlete, to plan results in certain types of decathlon for the next macrocycle of training and on this based on programming the training process for the upcoming annual cycle.